Factors Associated with Nurses' Fears in Caring for Patients with COVID-19 - Amelia Ganefianty; Sri Yona; Ismail Fahmi; Elly Nurachmah (Mashhad University of Medical Sciences, 2022)
Background: Nurses face a high risk of experiencing excessive fear while caring for patients with COVID-19. However, to our knowledge, no study has yet explored the factors associated with nurses' fears when caring for patients with COVID-19.Aim: The present study aimed to analyze the factors associated with nurses' fears when caring for COVID-19 patients in Indonesia.Method: This cross-sectional study was conducted on 591 nurses caring for COVID-19 patients. The nurses were recruited from 26 provinces in Indonesia using a purposive sampling method in April 2020. The instruments consisted of a sociodemographic characteristics form and a valid instrument to explore nurses' fears. Data were analyzed using SPSS software (version 23).Results: In total, 86.8% of the nurses felt fear when caring for COVID-19 patients. Moreover, despite using personal protective equipment, 83.8% of participants answered that they feared getting infected with the virus while caring for patients, and 87.5% of the participants feared that their families might become infected with the virus. Among the nurses who cared for COVID-19 patients, 91.2% feared they might pass the disease on to their families at home. Age, marital status, infection prevention control training, and nurses' education level were significantly related to nurses' fears (P<0.05, CI 95%).Implications for Practice: The excessive fear in nurses who care for COVID-19 patients is a major issue for nursing managers. Provision of viral transmission prevention and control programs, self-esteem improvement activities, and having pandemic course subjects in the nursing education curricula can help nurses become more aware and ready to face a pandemic.